Functionalization of a stable AIE-based hydrogen-bonded organic framework for white light-emitting diodes. Issue 36 (17th August 2022) - Lin, Yu-Xin; Wang, Jia-Xin; Liang, Cong-Cong; Jiang, Chenghao; Li, Bin; Qian, Guodong
Abstract : We successfully fabricated a white light-emitting diode by coating functionalized AIE-based HOF-76 material on a 460 nm blue LED chip. Abstract : Hydrogen-bonded organic frameworks (HOFs) have received tremendous attention in recent years due to the good designability. However, the pure organic nature of HOFs sometimes limits the application development and performance improvement. Functionalizing is an effective strategy to control and modulate material properties, which can achieve properties that cannot be achieved by a pristine material. Herein, a series of HOF-76⊃DSMI were synthesized through functionalizing the stable AIE-based HOF-76 by incorporating a red dye which complements the deficiency of the red component of HOF-76. Then, a single matrix white light-emitting diode (WLED) was fabricated by coating the HOF-76⊃DSMI material on a 460 nm blue LED with CIE chromaticity coordinates of (0.333, 0.329), a correlated colour temperature (CCT) of 5490 K and a colour rendering index (CRI) of 80.